2012
DOI: 10.2147/bctt.s26431
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy in breast cancer

Abstract: Tumor dormancy describes a prolonged quiescent state in which tumor cells are present, but disease progression is not yet clinically apparent. Breast cancer is especially known for long asymptomatic periods, up to 25 years, with no evidence of the disease, followed by a relapse. Factors that determine the cell's decision to enter a dormant state and that control its duration remain unclear. In recent years, considerable progress has been made in understanding how tumor cells circulating in the blood interact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Tumor dormancy is considered to be one trigger of late recurrence [23]. Tumor dormancy describes a prolonged quiescent state in which tumor cells are present, but disease progression is not yet clinically apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor dormancy is considered to be one trigger of late recurrence [23]. Tumor dormancy describes a prolonged quiescent state in which tumor cells are present, but disease progression is not yet clinically apparent.…”
Section: Discussionmentioning
confidence: 99%
“…While these models of dormancy are not mutually exclusive and might even coexist in the same patient, we will focus on cellular dormancy that is best supported by clinical evidence (Banys, Hartkopf, et al, 2012; Morrissey, Vessella, Lange, & Lam, 2015). Several studies showed that DTCs are frequently found in cancer patients with NED (Braun et al, 2005; Chery et al, 2014; Klein, 2009; Schardt et al, 2005), and the detection of DTCs in the bone marrow is associated with worse clinical outcome in many solid cancers (Braun et al, 2000; Hartkopf et al, 2014, 2015; Thorban, Rosenberg, Busch, & Roder, 2000; Wollenberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since patients with ovarian carcinoma rarely develop secondary bone metastases, bone marrow seems to serve as a temporary "compartment" for disseminated tumor cells, where they might stay dormant for prolonged periods of time [20,21]. Subsequently, they might be able to leave their homing site and cause metastatic growth or locoregional recurrence [6].…”
Section: Discussionmentioning
confidence: 99%